Real Exchange Rates and the Earnings of Immigrants - Christian Dustmann; Hyejin Ku; Tetyana Surovtseva (Institute of Labor Economics (IZA), 2023)
We relate origin-destination real price differences to immigrants' reservation wages and their career trajectories, exploiting administrative data from Germany and the 2004 enlargement of the European Union. We find that immigrants who enter Germany when a unit of earnings from Germany allows for larger consumption at home settle for lower entry wages, but subsequently catch up to those arriving with less favourable exchange rates, through transition to better-paying occupations and firms. Similar patterns hold in the US data. Our analysis offers one explanation for the widespread phenomenon of immigrants' downgrading, with new implications for immigrant cohort effects and assimilation profiles.
Keywords: J24; J31; J61; O15; O24; 330; real exchange rate; reservation wage; immigrant downgrading; earnings assimilation